Comparison of different PCR tests to identify Monilinia fructicola. (7th April 2015) - Riccioni, L.; Valente, M. T.
Abstract : Monilinia fructicola was until very recently a regulated pest in the European Union, and EU countries were requested to monitor its presence on their territories. As accredited laboratories should use validated tests, the mycological laboratory of CRA‐PAV carried out a validation process for the multiplex based PCR test (Coté et al ., 2004 ), that is one of the most widely used tests for the identification of M. fructicola, although this test is not described in the EPPO diagnostic protocol PM 7/18 (2) because the validation data were lacking. The performance characteristics of this multiplex PCR test were established according to the EPPO Standard PM 7/98 (1) and the test was compared in a collaborative study with the end point PCR test (Ioos & Frey, 2000 ), considered as the 'standard test'. The validation data were obtained using different isolates of M. fructicola, M. laxa, M. fructigena and Monilia polystroma, as well as different fruit tissues. Four series of the DNA target at different concentration, repeated three times, were analyzed in four Italian laboratories. The results showed that the multiplex PCR detection test (Coté et al ., 2004 ) was fit for diagnostic purpose, although the analytical sensitivity was significantly lower compared to the conventional PCR 'standard test'.